The paradox of awareness of bylaws in dealing with environmental consequences of urban livestock keeping in Tanzania - Mdendemi, Rehema Tiberio; Gwalema, Susan Rugano (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
This study examined the community awareness of urban bylaws on livestock keeping. It was conducted in two municipalities of Dodoma and Morogoro which had elaborate bylaws on urban livestock keeping. Primary data were collected at household level through interviews and focused group discussion. Secondary data on the other hand, were collected by reviewing various documents and bylaws on urban livestock keeping which were obtained from Municipal Offices (Agriculture and Livestock Department, Urban Planning and, Environment and Health Department) from libraries and from the Internet. Using a sample of 298 respondents whose majority were livestock keepers, it was found that 78.7% were not aware of the bylaws that guide urban livestock keeping. Awareness of bylaws by the respondents was closely associated with the number of extension staff and extension contacts. Other characteristics associated with the respondents such as level of education, occupation, gender and age were also highly associated with awareness of the bylaws. However, by-law enforcement mechanism had insignificant influence on awareness. Thus, the generally perceived notion that, urban dwellers are aware of bylaws that guide urban livestock keeping needs to be taken cautiously. In order for people to be aware of the bylaws and enforce them, they should participate in their formulation.